2009
DOI: 10.1002/cssc.200900199
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Catalytic Conversion of Fructose into 5‐Hydroxymethylfurfural in Ionic Liquids at Room Temperature

Abstract: One of the main challenges for establishing a society that uses biomass-derived carbohydrate chemistry will be the development of effective chemical transformations that are rapid and that can be performed at room temperature. Herein, we report a method for transforming fructose into 5-hydroxymethylfurfural (5-HMF) that is quantitative and operates at room temperature. The preparation of 5-HMF, which is a versatile, key renewable platform molecule from biomass-derived carbohydrates, is regarded as an essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(90 citation statements)
references
References 32 publications
(19 reference statements)
2
87
1
Order By: Relevance
“…Thus indicating that this process is catalyzed more effectively by a suitable Lewis acid rather than a Brønsted acid. The largest amounts of LA (23.9 wt%) and 5-HMF (3.95 wt%) produced in this set of reactions came from those using SnCl 4 ·5H 2 O (15) and BiCl 3 (12), respectively.…”
Section: Catalyst Screeningmentioning
confidence: 94%
“…Thus indicating that this process is catalyzed more effectively by a suitable Lewis acid rather than a Brønsted acid. The largest amounts of LA (23.9 wt%) and 5-HMF (3.95 wt%) produced in this set of reactions came from those using SnCl 4 ·5H 2 O (15) and BiCl 3 (12), respectively.…”
Section: Catalyst Screeningmentioning
confidence: 94%
“…27, 28 The application of ionic liquids in carbohydrates (lignocellulosic biomass) chemistry is relatively new and further studies combining these two fields are presented by Zakrzewska et al 29 Additionally, Qi et al also reported promising results when they studied the production of HMF from glucose and fructose catalyzed by TiO 2 and ZrO 2 under microwave irradiation.…”
Section: -23mentioning
confidence: 99%
“…[Cl] with different co-solvents such as DMSO, acetone, methanol, ethanol, ethyl acetate and supercritical carbon dioxide [32]. Fructose was first dissolved in ILs at 80C and added Amberlyst-15, a strong acidic ion-exchange resin catalyst, and co-solvent was added to give a gel-like mixture after cooling.…”
Section: Qi Et Al Employed Ionic Liquid [Bmim]mentioning
confidence: 99%
“…Fructose was first dissolved in ILs at 80C and added Amberlyst-15, a strong acidic ion-exchange resin catalyst, and co-solvent was added to give a gel-like mixture after cooling. It was demonstrated that the reaction could proceed at an ambient temperature of 25C with yields of 78% -82% for 5-HMF [32].…”
Section: Qi Et Al Employed Ionic Liquid [Bmim]mentioning
confidence: 99%